British Thoracic Society guideline for respiratory management of children with neuromuscular weakness: commentary. Issue 7 (20th June 2012) - Hull, Jeremy
Abstract : The British Thoracic Society guideline for respiratory management of children with neuromuscular weakness summarises the available evidence in this field and provides recommendations that will aid healthcare professionals in delivering good quality patient care.